PENINGKATAN KUALITAS PELAYANAN TRANSPORTASI PADA PENYEBERANGAN LINTAS KALIANGET-TALANGO DALAM UPAYA MEMENUHI KEBUTUHAN MASYARAKAT (Studi pada UPT. Pelabuhan Dinas Perhubungan Kabupaten Sumenep) - Melly Oktavia; Irma Irawati Puspaningrum; Yayak Nurwahyudi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2014)
This study aimed to determine the extent of improvement in the quality of transport services crossing Kalianget cross-Talango in an effort to meet the needs of the community. This research is based on data taken in UPT. Pelabuhan Dinas Perhubungan Kabupaten Sumenep This study used a qualitative research method with data collection using in-depth interviews with informants, gathering data from documents and records, and obtaining data by direct observation of the phenomenon under study. The results of the study consists of three quality of service in improving the operation of services for the community that first crossing, associated with the responsiveness of each personnel boat to some of the things that happened during the crossing activity. Secondly, in relation to responsibility, services crossing under the provisions applicable. Third, related to the accountability of service providers crossings in accordance with the interests of stakeholders and developing norms in society. Keywords: Quality of Care, Transportation, UPT. Pelabuhan Dinas Perhubungan Kabupaten Sumenep